Improving supply chain management process using design structure matrix based cross‐functional analysis. Issue 4 (18th March 2019) - Son, Samuel; Kim, Junhong; Lee, Jangwon; Ahn, Jaemyung
Abstract: This paper introduces a process improvement study for a supply chain management (SCM) system of an aircraft manufacturer by using the design structure matrix (DSM). A high‐level model for the overall SCM process has been set up. Information and operation interfacing between critical tasks (CTs) belonging to adjacent steps of the high‐level models are expressed and analyzed using the DSM. The interface values (IVs), which represent the extent of risk exposure of the interfaces, are computed. The IVs associated with DSM cells are used to identify high‐impact cross‐functional areas of the system. The gray areas, which present opportunities for improvements in the system performance, are found after an in‐depth gap analysis of the identified high‐impact areas. Finally, the measures that can address the gaps in the gray areas and improve the system process are developed. The results and insights obtained from a process improvement case study on SCM of the Boeing Company are discussed.